Odor encoder: computational design of a novel allosteric enzyme activation system for providing enhanced olfactory abilities to trained odor detecting sentinel animals - Scroggins, Michael, author; Snow, Christopher, advisor; Peebles, Christie, advisor; Gentry-Weeks, Claudia, committee member (Colorado State University. Libraries, 2022)
From the perfume of a flower, to the aroma of a favorite food, to what for bioengineers is the all-to-familiar smell of E. coli, olfactory senses play in important role in how animals interact with the world around them. An offensive odor can inform us that an object is unsafe to eat or be around, a familiar scent can recall memories of events from decades in our past, and even our natural body odors can affect our mating selection preferences. Yet there are many chemicals, both natural and synthetic, for which we do not possess the ability for olfactory detection. An everyday example of this is the natural gas that we use in our homes and which is naturally odorless, but which is commonly spiked with the odorant tert-butyl mercaptan (TBM) to provide the characteristic sulfuric smell we associate with natural gas. Because of this added odorant we can rapidly detect a leaking gas via the smell of the TBM and address the situation as needed to ensure the safety of ourselves and our community. Unfortunately, there are some hazardous and odorless chemicals which we cannot simply spike with an odorant molecule, and for these situations it would be ideal to have alternative options for facilitating a rapid olfactory detection. Therein lies the goals of the Odor Encoder project; to create enhanced olfactory abilities via a conditionally activated enzyme which produces a smellable product in the presence of a target odorless molecule. The approach to achieving this goal was creation of a genetically modified bacterial organism which could be engineered for conditional expression of an odorant producing enzyme in-situ within the nasal microbiome of trained odor detecting animals. The odorant producing enzyme chosen for this purpose was salicylic acid methyltransferase, a.k.a SAMT, which produces the characteristic odorant molecule methyl salicylate via methylation of salicylic acid. The probiotic E. coli strain Nissle 1917 was selected as the bacterial organism for inoculation of the nasal microbiome, and an expression plasmid was created which could produce both salicylic acid and methyl salicylate from endogenously produced metabolites via dual expression of SAMT along with a salicylate synthase enzyme known as irp9. Conditional production of methyl salicylate was achieved via two methods. The first method involved conditional enzyme expression via use of a riboswitch specific to the small molecule theophylline. The second method involved conditional enzyme activity via constitutive expression of a crippled form of SAMT which may potentially have its enzymatic activity restored via theophylline induced allosteric activation. The allosteric rescue method utilized computational design methods to design novel theophylline-specific allosteric cavities in SAMT, and theophylline induced allosteric reactivation of enzyme activity will be investigated via production and screening of the computationally designed enzyme library.
Keywords: computational design; olfaction; sentinel species; enzyme; allostery; salicylic acid methyltransferase